PENINGKATAN PRESTASI BELAJAR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) PADA MATA PELAJARAN KOMPETENSI KEJURUAN KELAS X SMK NEGERI 3 TAKALAR - Lanuihsan, Lanuihsan; Nur, Hasanah; Irfan, Andi Muhammad (Universitas Negeri Makassar, 2015)
This is a Classroom Action Research, to knowthe Â increase of students achievement in vocational competency ofclass X ATPH I SMK 3Takalar. The researchâ€™s subject are 32 students in class X ATPH I SMK 3Takalar at 2014/2015.This research performed in 2 cycles and each cycle consist of 4 times meeting. The data connected frompre-test and post-test at the end of each cycle. Classically completeness in the pre-test 31,25%. In the first cycle student achievement increase 37.5%so that classically completeness become 68.75% and the second cycle students achievement increase 21.87% so that classically completeness become 90.62%. Based on the results, group investigation (GI) learning model can improve student achievement of vocational competency of SMK Negeri 3 Takalar